Conversor multinível ponte-H em cascata aplicado a um gerador eólico com bobinas abertas - Samuel dos Santos Bettoni (2023)
In recent years there has been a growing expansion of renewable sources around the world, with wind energy being among the most stand out. With the advances of technology, wind turbine projects have considerably increased their power, reaching the present day in power of up to 15 MW, mainly for offshore installations. One of the main challenges of high-power wind energy conversion systems (WECS) is the power converters, more specifically the semiconductor components, which have limited voltage and current capabilities. In this context, several works have been developed about of multilevel converters, whose purpose is to increase voltage levels, thus carrying higher power levels. Among the structures of multilevel converters, the most employed are: the neutral point clamped (NPC), the flying capacitor (FC) and the cascaded H-bridge (CHB). In addition to the application of multilevel converters, it is possible to increase the voltage and power levels employing an open-end winding (OEW) connection to the generator. This work aims to investigate the application of cascaded H-bridge converters providing a five-level structure, driving a squirrel-cage induction machine in open-end winding configuration connected to a wind energy conversion systems. Simulation results using the PLECS software demonstrate the application in a wind system of 1.677 MW, voltage of 1.15 kV . The modulation technique used for the multilevel converters in this work resulted in a low harmonic content in the machine currents, as well as in the current injected into the power grid. In addition, it was possible to verify the power distribution between the converters, demonstrating that lower power converters can be combined to achieve higher power in the WECS.